2017
DOI: 10.1093/ijnp/pyx058
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin reduces cocaine cued fos activation in a regionally specific manner

Abstract: BackgroundOxytocin may be a possible treatment for multiple neuropsychiatric disorders, including cocaine addiction. Little is known about the site-specific effects of oxytocin on various drug addiction-related brain regions. Furthermore, sexually dimorphic effects of oxytocin on neural function in the addiction circuit have not been established. Here, we studied Fos expression following cocaine-cued reinstatement in both male and female rats.MethodsMale and female rats underwent self-administration, extinctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 69 publications
(97 reference statements)
6
36
2
Order By: Relevance
“…A previous study from our lab (Cox et al, 2017) demonstrated that an oxytocin receptor antagonist infused into the NAcore blocked the effects of systemic oxytocin. Further, we have shown that systemic administration of oxytocin normalizes conditioned cued-induced fos expression within the addiction cirtictry (Leong et al, in press). While the precise mechanism of oxytocin in the NAcore remains to be determined, our finding that mGluR2/3 antagonism blocks oxytocin’s impact on cued meth seeking suggests oxytocin may modulate presynaptic glutamate function.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A previous study from our lab (Cox et al, 2017) demonstrated that an oxytocin receptor antagonist infused into the NAcore blocked the effects of systemic oxytocin. Further, we have shown that systemic administration of oxytocin normalizes conditioned cued-induced fos expression within the addiction cirtictry (Leong et al, in press). While the precise mechanism of oxytocin in the NAcore remains to be determined, our finding that mGluR2/3 antagonism blocks oxytocin’s impact on cued meth seeking suggests oxytocin may modulate presynaptic glutamate function.…”
Section: Discussionmentioning
confidence: 96%
“…Taken together, this evidence indicates that systemic oxytocin is producing its effects via a central mechanism; however, the mechanisms that produce these effects are unclear. Systemic oxytocin activates oxytocin cell bodies in the paraventricular nucleus (PVN) (Carson et al, 2010b; Leong et al, in press). This activation results in local dendritic release of oxytocin and an ensuing positive-feedback effect promoting prolonged activation of the oxytocin system (Ludwig et al, 2002; Rossoni et al, 2008), which is presumed to cause brain wide oxytocin release, including areas associated with addiction.…”
Section: Discussionmentioning
confidence: 99%
“…In general, peripheral oxytocin administration attenuates lever pressing during a cocaine-primed reinstatement test and cue-induced reinstatement tests in male (Bentzley et al, 2014; Zhou et al, 2014) and female rats and this reduction is not dependent on cycle (Leong et al, 2016; Leong et al, 2017; Weber et al, 2018). Central infusions of oxytocin (icv) also attenuate cue-induced cocaine-seeking behavior in both sexes (Leong et al, 2017; Morales-Rivera et al, 2014). Recent studies have begun to highlight specific neural regions that may be mediating oxytocin’s central effect on cocaine-seeking behavior.…”
Section: Oxytocin Effects On Preclinical Models Of Addictionmentioning
confidence: 91%
“…However, CRF responses to stressors are differently modulated by the two major 'social' hormones oxytocin (OT) and arginine vasopressin (AVP) (Stoop, 2012). Interestingly, studies have also shown that administration of vasopressin or OT decreases cocaine self-administration or cue-induced reinstatement of cocaine seeking in rats respectively (van Ree et al, 1988;Leong et al, 2017). Interestingly, CRF 2 receptors are expressed both in the PVN and the supraoptic nucleus of the hypothalamus (SON), main sources of OT and AVP production in the brain (Van Pett et al, 2000;Stoop, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cocaine withdrawal increased the expression of PVN-AVP, OT receptor binding in the medial and lateral septum and the amygdala, decreased novel object recognition memory and increased anxiety-like behaviour in mice and rats (Zhou et al, 2011;Georgiou et al, 2016b). Interestingly, studies have also shown that administration of vasopressin or OT decreases cocaine self-administration or cue-induced reinstatement of cocaine seeking in rats respectively (van Ree et al, 1988;Leong et al, 2017). Nevertheless, the role of the CRF/CRF 2 receptor system in social behaviour deficits and brain AVP/OT changes induced by stimulant substances remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%